Synthesis and photocatalysis of ZnO/Fe2O3 nanocomposite in degrading herbicide 2,4-dichlorophenoxyacetic acid - Lee, Kian Mun; Abdullah, Abdul Halim; Hussein, Mohd. Zobir; Zainal, Zulkarnain (Universiti Kebangsaan Malaysia, 2014)
ZnO/γ-Fe2O3 catalysts were fabricated via a simple precipitation route using zinc acetate and iron acetate as the precursors and ammonia as the precipitant. The resulted nanocatalysts were subjected to heat treatment at 450°C for 2 h. The characteristics of the nanocomposite were investigated by various characterization techniques. The synthesized nanocomposite has an average particle size of 13 nm and a surface area of 17 m2/g. The photocatalytic activity of ZnO/γ-Fe2O3 nanocomposite was evaluated by photodegrading 2,4-dichlorophenoxyacetic acid (2,4-D) under UV irradiation. The results showed that ZnO/γ-Fe2O3 nanocomposite exhibited enhanced photoactivity compared to pure ZnO with almost 20% increment within 4 h of reaction time. The result indicated the applicability of ZnO/γ-Fe2O3 nanocomposite to be used as photocatalyst in removing organic pollutants in wastewater.